A Novel Soluble Squalene-Hopene Cyclase and Its Application in Efficient Synthesis of Hopene - Liu, Zhen; Zhang, Yinan; Sun, Jianan; Huang, Wen-Can; Xue, Changhu; Mao, Xiangzhao (Frontiers in Bioengineering and Biotechnology, 2020)
Hopene is an important precursor for synthesizing bioactive hopanoids with great commercial value. However, the chemical methods for synthesizing hopene are not efficient to date. Hopene is commonly obtained by extracting from plants or bacteria like other terpenoids, but the complicated extraction process is inefficient and unfriendly to the environment. Hopene can be biological synthesized by squalene-hopene cyclase (SHC) from squalene. However, hopene production by SHC remained at a low level until now. In this work, we found a novel SHC named OUC-SaSHC from Streptomyces albolongus ATCC 27414. An easy procedure for expression and purification of OUC-SaSHC was established. The conditions for OUC-SaSHC to convert squalene into hopene are optimized as in 100 mM sodium phosphate buffer (pH 7.0) containing 0.5% Tween 80, 20 mM squalene and 0.14 mg/mL OUC-SaSHC at 30 °C. In the scale-up reaction with the final volume of 100 mL, the yield of squalene could be up to 99% at 36 h, and 8.07 mg/mL hopene was produced. Our work showed a great potential of OUC-SaSHC as biocatalyst on scale-up production of hopene, hence improves the SHC-catalyzing enzyme synthesis of hopene from laboratory level to application level.